1982
DOI: 10.1002/j.2164-4918.1982.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Interest, Running, and Life Adjustment

Abstract: High social interest persons and runners reported significantly higher life adjustment scores than did low social interest persons and nonrunners. The interaction effect, however, was not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There are numerous benefits associated with being generous and helping others, including less depression, distress, and hopelessness, greater relationship satisfaction, higher self-esteem, greater perceived meaning and purpose in life, and better health (Baumeister, 1991; Crandall, 1980; Miller, Denton, & Tobacyk, 1986; Schwartz & Sendor, 2000; Zarski, Bubenzer, & West, 1982). Notably, these benefits of helping are also associated with reduced depression and improved well-being (Baumeister, 1991; Taylor & Turner, 2001).…”
mentioning
confidence: 99%
“…There are numerous benefits associated with being generous and helping others, including less depression, distress, and hopelessness, greater relationship satisfaction, higher self-esteem, greater perceived meaning and purpose in life, and better health (Baumeister, 1991; Crandall, 1980; Miller, Denton, & Tobacyk, 1986; Schwartz & Sendor, 2000; Zarski, Bubenzer, & West, 1982). Notably, these benefits of helping are also associated with reduced depression and improved well-being (Baumeister, 1991; Taylor & Turner, 2001).…”
mentioning
confidence: 99%
“…Mean age for the entire sample was 31.0. Zarski, West, and Bubenzer (1982) reported support for hypotheses one and two, but no support for the third hypothesis.…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 92%
“…The correlations suggested that the alcoholics with higher social interest are motivated more by the achievement of success than by the avoidance of failure and vice versa for the alcoholic with low social interest. Mozdzierz and Semyck (1981) Zarski, West, and Bubenzer (1982) examined the relationship between social interest as measured by the SII and adjustment with a sample that contained runners and nonrunners. The authors predicted that runners would report greater life adjustments as measured by the Bell Adjustment…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 99%